2018
DOI: 10.1186/s12875-018-0841-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between family physician’s direct advice and pneumococcal vaccination intention and behavior among the elderly in Japan: a cross-sectional study

Abstract: BackgroundVaccination is an important element of health maintenance in family medicine. The 23-valent pneumococcal polysaccharide vaccine (PPSV23) is highly recommended for the elderly, but its uptake is low in Japan. Primary care system remains under development and preventive services tend to be neglected in the Japanese medical practice. The study aims to investigate the association between family physician’s recommendations for PPSV23 during outpatient care and PPSV23 vaccination intention and behavior in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
1
26
0
1
Order By: Relevance
“… 18 In another questionnaire-based study, Higuchi et al looked at PPSV23 rates and motivations among elderly adults receiving regular outpatient care, and found doctors’ advice to positively correlate with vaccinated status. 19 We observed doctors’ recommendations to significantly and strongly predict PPSV23-vaccinated status in all three age groups in the present study. In addition, PPSV23’s inclusion in Japan’s routine immunization schedule for elderly adults appears to have been the major reason for coverage observed in the 65+ age group.…”
Section: Discussionsupporting
confidence: 56%
“… 18 In another questionnaire-based study, Higuchi et al looked at PPSV23 rates and motivations among elderly adults receiving regular outpatient care, and found doctors’ advice to positively correlate with vaccinated status. 19 We observed doctors’ recommendations to significantly and strongly predict PPSV23-vaccinated status in all three age groups in the present study. In addition, PPSV23’s inclusion in Japan’s routine immunization schedule for elderly adults appears to have been the major reason for coverage observed in the 65+ age group.…”
Section: Discussionsupporting
confidence: 56%
“…HCPs are the forefront for improving immunization rates as their recommendation is the greatest motivation. 11,16 It works equally effective as compared to the time and efforts spent on counselling and other preventive services.…”
Section: Discussionmentioning
confidence: 99%
“…The survey questionnaire comprised of questions for HCPs which embraced the knowledge, practices and barriers for pneumococcal, influenza and hepatitis-B vaccination in adults with type-2 DM based on previous studies. 11,12 The questions were designed based on logic framework for vaccine preventable diseases, provided by Centres for Disease Control and Prevention (CDC)based "The Guide to Community Preventive Services", developed under the leadership of Task Force on Community Preventive Services. 14,15 The design had taken into consideration the following aspects: (a) provider-based Perception (e.g.…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…26 A study among Japanese primary care physicians found that patients who had pneumococcal vaccination were more likely to have received advice from physicians than those who did not receive such advice (80% vs 21%), and a strong association was shown between physician recommendation and patient participation in vaccination with an adjusted odds ratio of 8.50. 27 A study in France demonstrated that patients who received recommendations from trusted family physicians were more likely to participate in HPV vaccination programme. 28 In Hungary, physicians effectively motivated approximately 27% of women who initially refused to join cervical cancer screening programmes.…”
mentioning
confidence: 99%